New Contributions in Generalization S-Metric Spaces to S∗p-Partial Metric Spaces with Some Results in Common Fixed Point Theorems - Asma Al Rwaily; A. M. Zidan (Complexity)
In this paper, we introduce the notion of S∗p-partial metric spaces which is a generalization of S-metric spaces and partial-metric spaces. Also, we give some of the topological properties that are important in knowing the convergence of the sequences and Cauchy sequence. Finally, we study a new common fixed point theorems in this spaces.